Sistema de Vigilância de Infecção Hospitalar do Estado de São Paulo Ano 2011 - Brandão de Assis, Denise; Madalosso, Geraldine; Ferreira, Sílvia Alice; Y. Yassuda, Yara; Monteiro Polachini, Zuleida (BEPA. Boletim Epidemiológico Paulista, 2012)